2010
DOI: 10.1063/1.3490758
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar resistive switching behaviors in amorphous lutetium oxide films

Abstract: Articles you may be interested inUnipolar resistive switching in insulating niobium oxide film and probing electroforming induced metallic components Electrically induced conducting nanochannels in an amorphous resistive switching niobium oxide film Appl. Phys. Lett. 97, 233509 (2010); 10.1063/1.3525710Forming-free colossal resistive switching effect in rare-earth-oxide Gd 2 O 3 films for memristor applications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…At the same time, much work and research is currently being carried out to speed up the integration of ReRAM devices [2], so if we look at the future, exploring materials that can be used in ReRAM applications is quite relevant. In addition to the Perovskite-type oxides [8], NiO [9] and TiO 2 [10], which are the most widely investigated oxides in the world, many oxides have recently been reported that show monopoplar and/or bipolar ReRAM switching properties [11][12][13][14][15][16][17][18][19][20][21]. Our present investigation of molybdenum oxide is in this same research category.…”
Section: Introductionmentioning
confidence: 89%
“…At the same time, much work and research is currently being carried out to speed up the integration of ReRAM devices [2], so if we look at the future, exploring materials that can be used in ReRAM applications is quite relevant. In addition to the Perovskite-type oxides [8], NiO [9] and TiO 2 [10], which are the most widely investigated oxides in the world, many oxides have recently been reported that show monopoplar and/or bipolar ReRAM switching properties [11][12][13][14][15][16][17][18][19][20][21]. Our present investigation of molybdenum oxide is in this same research category.…”
Section: Introductionmentioning
confidence: 89%
“…Rare earth metal oxides as high-Îș dielectrics are considered as the replacement of hafnium-based technology [ 17 - 19 ], among which Lu 2 O 3 is the promising one as it shows well-insulating property, large bandgap (5.5 eV), better hygroscopic immunity, good thermal stability, and adequate dielectric constant of approximately 11 [ 20 ]. Gao et al reported promising unipolar RS behavior in amorphous Lu 2 O 3 oxide [ 21 ]. In contrast, we previously demonstrated the bipolar RS in various high-Îș rare earth metal oxides, such as Tm 2 O 3 , Yb 2 O 3 , and Lu 2 O 3 , on silicon substrate [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In OxRRAM, the resistive switching mechanism is governed by formation and annihilation of conductive filaments formed by either oxygen vacancies or movement of ions inside the RRAM devices [7]. However, in CBRAM, a metal cation is necessary to develop resistive switching behavior by constructing and destructing the conductive bridges formed through electrochemical process [8][9][10][11]. Moreover, it is mandatory for IT industry to enhance electrical characteristics by exposing MOSFETs to high temperature annealing [12].…”
Section: Introductionmentioning
confidence: 99%